Aesthetic results were more satisfactory after oncoplastic surgery than after total breast reconstruction according to patients and surgeons - Lisboa, Fabiana Christina Araújo Pereira (2023)
Introduction: Patient satisfaction after breast cancer surgery has an impact on body image, sexual function, selfesteem, and quality of life and may differ from the perception of the attending physician. This study aimed to compare the aesthetic outcomes and satisfaction with conservative oncoplastic surgeries, mastectomies, and total breast reconstruction. Methods: We included 760 women diagnosed with invasive breast carcinoma or phyllodes tumors who returned at least 6 months after surgery or radiotherapy at two public hospitals and a private clinic between 2014 and 2022. Data was collected prospectively from patients and retrospectively from their medical records using a specific form after obtaining their informed consent. Aesthetic outcomes and quality of life were assessed using the BREAST-Q©, Harris Scale, and BCCT.core software. Data were evaluated using the SPSS statistical software. Statistical significance was set at p < 0.05. This study was approved by the hospital ethics committees. Results: A total of 405 (53.29%) partial and 355 (46.71%) total reconstructions were included. Patients who underwent partial reconstruction were older and had higher body mass index. Patients who underwent total reconstruction had larger tumors with advanced clinical and pathological stages. Clinical and surgical complications occurred more frequently in the total reconstruction group. A greater number of reparative surgeries and lipofilling procedures were required for total reconstruction. According to the BREAST-Q, the partial reconstruction group showed significantly higher levels of women’s satisfaction with their breasts, the surgical outcomes, psychosocial and sexual well-being, provision of information, and the reconstructive surgeon. Only physical well-being was slightly higher in the total reconstruction group. In most cases, the results were rated good or excellent. Physicians considered partial reconstructions to have better results than total reconstructions, although this difference was not perceived by the BCCT.core software. Conclusion: Women who underwent partial breast reconstruction had higher levels of satisfaction in several domains, lower frequency of complications, and required fewer surgeries to complete their reconstruction than women who underwent total reconstruction. Physicians were also more satisfied with the results of partial reconstructions.